Legal Review of The Implications of The Principle of Dominus Litis for Prosecutors with Restorative Justice Efforts in Criminal Justice Processes (Research Study at The West Halmahera District Attorney's Office) - Soeroso, Raka Aprizki; Gunarto, Gunarto (UNISSULA Semarang, 2025)
Currently, the legal system in Indonesia is experiencing development. This development emphasizes the orientation of criminal case resolution which was initially based on the retributive paradigm that provides retribution for crimes committed by the perpetrator towards a new approach model, namely